Merleau-ponty'de bedenlenmiş özne. - Koç, Çağlar (Felsefelogos, 2025)
In this article, we would like to present Merleau-Ponty's conception of the embodied subject, which has made an extremely important contribution to the discussion of the subject in phenomenology, and to question whether the descriptions that form the basis of this conception actually correspond to our experience of the body. It is generally accepted that a phenomenological inquiry that takes the body into account must be done in an 'externalist' way. However, it is not clear what is meant by 'external' here. In the first part of our article, we will try to clarify the meaning of this word. This first part aims to prepare us for Merleau-Ponty's thought. In the second part, we will focus on the invisible spatiality of the body that resists the classical definition of space. In the third and final part, we will focus on the concept of 'awareness' in relation to the embodiment of the subject and question how this term is understood in Merleau-Ponty and how it should be understood in reality.